'Powers' in Rom 13,1-7: Angels or Magistrates? - Fogielman, Charles-Antoine (Biblica, 2022)
This paper seeks to add a new perspective to the vexed question of whether the words ἄρχοντες or ἐξουσίαι in Rom 13,1-7 refer to angelic beings or Roman magistrates. Instead of adjudicating the debate one way or another, literary analysis is used to show how the polysemy of such vocabulary is put to profit in order to advance the rhetorical aims of the passage.